Impact of training and development on employee’s performances – “A Study on Mutual Trust Bank Limited - Jaci, Taslimun Jannath (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.